IMPLEMENTASI METODE PROTOTYPING PADA RANCANGAN TOKO TANAMAN BERBASIS ANDROID: IMPLEMENTATION OF THE PROTOTYPING METHOD IN ANDROID-BASED PLANT STORE DESIGN - Muhamad Alda; Muhammad Hendrik Koto; Anggika Wardani (LPPM Universitas Abdurrab, 2023)
Entrepreneurs today are faced with the demand to innovate and have a deep understanding of increasingly sophisticated technology so that they can survive in the competition. One of the business sectors that must survive is the plant business. The plant shop itself sells a variety of seeds, plant seeds, and a variety of plants with cheap to expensive price variants. One of the common problems faced by shop owners is the difficulty of accessing information about plant shops that match the user's wishes. This also applies to shop owners who mostly still promote their plant shops conventionally through brochures, flyers, social media, and so on. Given these complaints and problems, an Android-based plant shop application is needed. This application has been developed using the prototyping method. By applying the prototyping method, users have an active role that makes implementing the system easier. The implementation of this application aims to provide store search facilities that are integrated with GPS using Google Maps, facilitate the plant transaction process, and help plant entrepreneurs in managing and marketing their stores optimally. In the implementation of this application is expected to provide convenience for sellers and plant shop owners in utilizing the plant shop application. The results of testing conducted on ten users show that this application is 53% satisfactory and feasible to use by users, namely plant shop admins and customers.